THU0358 Usefulness of 18f-fdg positron emission tomography (PET) for lymphoma diagnosis in patients with primary sjÖgren's syndrome. (12th June 2018) - Keraen, J.; Blanc, E.; Besson, F.; Meyer, M.; Le Guern, V.; Nocturne, G.; Henry, J.; Belkhir, R.; Mariette, X.; Seror, R.
Abstract : Background: Primary Sjögren's syndrome (pSS) is the autoimmune disease having the highest risk of lymphoma. The differential diagnosis between benign and malignant lymphoproliferation is sometimes difficult. Among imaging procedures, 18F-FDG PET could be useful for that purpose. Objectives: To compare 18F-FDG PET results between patients with and without lymphoma to identify PET pattern associated with lymphomas in pSS Methods: Retrospective study conducted in 2 centres including pSS patients (according to ACR/EULAR 2016 criteria) who undergo 18F-FDG PET. We compared PET abnormalities in patients with and without lymphoma, the PET having been done before any chemotherapy. Two independent readers analysed PET blind to lymphoma diagnosis. ESSDAI-PET score previously described by Cohen et al. [ 1 was calculated. Results: 45 patients were included; 15 had lymphoma: MALT (n=12), nodal marginal zone with plasmacytic differentiation (n=2), diffuse large B-cell (n=1). Patients with lymphoma had more frequently parotid gland swelling (67% vs 20%, p=0.003) and higher ESSDAI score (24 [13.5–29] vs 9, 5–20 p=0.03), even after exclusion of lymphoma item (19 11–27 VS 9, 5–20 p=0.03). Compared to non-lymphoma patients, mean size (45.5 38–56 mm vs. 40 37–41 mm; p=0.048) and maximum standardised uptake value (SUVmax) of the parotid glands (5.6 [5–6.9] vs 3.8 [3.2–4.4]; p=0.001) were higher in lymphoma patients. 53.3% of patients with lymphoma and 43.3% without lymphoma had lymph node FDG uptake, but neither their number nor their repartition or mean SUV differ between them. Pulmonary uptake was observed in 6 (40%) patients with lymphoma and 6 (20%) without lymphoma (p=0.17). But in lymphoma patients, this uptake was focal in 5 (33.3%) patients (nodules or condensation) c and in only one (3.3%) patient without lymphoma (p=0.01). Remaining patients had interstitial FDG uptake. Mean PET score (4 2–4 vs. 2 1–3 p=0.04) and SUVmax at any site (6.3 [5.6–7.3) vs. 4.2 [3.7–5.9] p=0.02) were significantly higher in lymphoma group. 20 patients had PET guided biopsy of a hypermetabolic lesion that conducted to lymphoma diagnosis in 7 cases (46.6%). After chemotherapy for lymphoma, PET was available for 10 patients: complete regression of hypermetabolic lesions was observed in 6 patients (60%), and decreased uptake intensity in the 4 remaining patients. Conclusions: Some of the systemic manifestation of pSS (lung, lymph nodes and salivary glands) can be assessed by 18F-FDG PET. Lymph nodes hypermetabolism is frequent and not associated with lymphoma. The 18F-FDG PET abnormalities associated with lymphoma diagnosis are SUV max at any site >6, SUV max of parotid glands>5 and focal nodular hypermetabolic lung lesions. Finally, PET can be helpful to guide biopsy toward the most hypermetabolic structure for diagnosing lymphoma. Reference: [1] Cohen C, Mekinian A, Uzunhan Y, Fauchais A-L, Dhote R, Pop G, et al. 18F-fluorodeoxyglucose positron emission tomography/computer tomography as an objective tool for assessing disease activity in Sjögren's syndrome. Autoimmun Rev. 2013Sep;12(11):1109–14. Disclosure of Interest: None declared